MEDIA LITERACY-BASED AND PROJECT-BASED SYLLABUS FOR THE ENGLISH IN MEDIA DISCOURSE SUBJECT - Agustina, Imas Wahyu (Pusat Asesmen dan Pembelajaran, 2021)
Education at the higher levels is now encouraged to implement the 21st century learning and outcome-based education to enable the graduates to ready perform at the workplace. Moreover, the English Language Education Study Program of the State University of Jakarta is now undergoing a curriculum renewal to fit the 21st century demands. Thus, this first-year Research and Development (R&D) research design was conducted to develop a media literacy-based and project-based syllabus for the English in Media Discourse subject. Content analysis to the existing syllabus, clarified by the questionnaire and focus group discussion, was done to see the incorporation of the indicators of media literacy based and project-based learning. The results revealed that 48% of media literacy skill indicators were incorporated in the existing syllabus but no project-based activity was available. Therefore, the researcher proposed a syllabus to the subject that could best fit the demand of media literacy skills and implement a project-based learning to fully develop the students’ required skills for the 21st Century English learning. It is hoped that the results of this research can be applied in the Media Discourse related subjects in any universities. This syllabus will furthermore become the framework for the e-module development on the next stage of the research.